The choice between uniqueness and conformity in mass customization. (30th July 2018) - Zaggl, Michael A.; Hagenmaier, Markus A.; Raasch, Christina
Abstract : Extant research emphasizes that consumers use mass customization toolkits to create products they consider to be unique, and that perceived uniqueness is an important part of customer value. This research investigates the conditions of the customer's quest for uniqueness. It is motivated by the observation that decisions are often driven by others' choices and a desire to fit in, rather than to be distinct. We hypothesize that consumers are more inclined to choose uniqueness for hedonic product attributes but tend toward conformity in utilitarian attributes, and that consumers' need for uniqueness and product involvement moderate the choice. In a series of experiments, we find support for most hypotheses. We introduce conformity as a driver of choice behavior in mass customization toolkits and suggest that mass customization can best be seen as enabling consumers' preferred mix of uniqueness and conformity. Our results also inform managerial practice, highlighting that mass customization toolkits should consider customers' uniqueness and conformity requirements. We suggest reducing the number of utilitarian options while increasing the variety for hedonic attributes.